A STUDY ON THE USE OF YOUTUBE AS A MEDIA TO PROMOTE STUDENTS’ AUTONOMOUS LEARNING - Ismail, Widya Sari; Samtidar, Samtidar; Farahdiba, Syarifah (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This research aimed to describe the students’ perceptions of how YouTube promotes students’ autonomous learning. The researchers applied qualitative descriptive methods to achieve the research objective. The instrument used in the data collection was an interview guideline. The subjects of this research were students in English Education Study Program in the 2nd, 4th, and 6th semesters 2019 to 2021 academic years of Universitas Negeri Makassar. The interview sample was 6 students using the purposive sampling technique. Based on the results of this study, the researchers found that YouTube can promote students’ autonomous learning. YouTube is considered flexible, authentic, and motivating as a media to learn. It also enabled students to have the freedom to control their learning prosses. Nevertheless, students face challenges in using YouTube as a media for independent English learning.